Pengaruh Regulasi Diri Terhadap Fear of Missing Out (FoMO) Pada Mahasiswa Universitas Bhayangkara Jakarta Raya - Tiara, Nurul; Abdillah, Rijal (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
As a social network user, when something is trending, someone definitely wants to follow and doesn't want to be left behind by existing trends, including students. The fear of missing out is an indication of Fear of Missing Out (FoMO). There are several factors that influence the presence of Fear of Missing Out (FoMO), one of which is self-regulation. This study aims to determine the effect of self-regulation on Fear of Missing Out (FoMO) at University of Bhayangkara Jakarta Raya. The method used in this study is a quantitative method and uses a cluster sampling technique. The research instrument used the self-regulation scale and the Fear of Missing Out (FoMO) scale. The results of a simple linear regression test show that the regression coefficient is 0.246 and the coefficient of determination (R Square) is 0.096 with a significance of 0.002 (p <0.5) which indicates the effective contribution of the two variables is 9.6% and the rest is influenced by variables or other factors not examined in this study. The coefficient value shows a positive value, so it can be interpreted that self-regulation has a positive effect on Fear of Missing Out (FoMO). As for suggestions for further research in order to be able to expand the respondent's research further and use other factors that affect Fear of Missing Out (FoMO) besides Self-Regulation, so that research on Fear of Missing Out (FoMO) can develop.